A STUDY ON THE RELATIONSHIP BETWEEN PERFORMANCE MANAGEMENT AND EMPLOYEE RETENTION IN START-UP COMPANIES - Ginting, Sunardi; Retnowati, Eli; Aslichah, Aslichah; Rahayu, Betty; Mere, Klemens (Journal of Economic, Bussines and Accounting (COSTING), 2024)
This literature review examines the relationship between performance management and employee retention in start-up companies. In the competitive landscape of start-ups, retaining talented employees is crucial for sustaining growth and innovation. Effective performance management systems, which include regular feedback, clear performance metrics, and employee development opportunities, have been identified as vital components in enhancing employee satisfaction and loyalty. This study synthesizes findings from various research articles published post-2019, highlighting how robust performance management practices can lead to improved employee engagement and retention rates. Furthermore, it explores the unique challenges faced by start-ups in implementing these systems, such as limited resources and evolving organizational cultures. By analyzing the interplay between performance management and retention strategies, this review provides insights for start-up leaders seeking to foster a committed workforce. The findings underscore the importance of aligning performance management initiatives with employee expectations and organizational goals to create a sustainable business environment. Future research should focus on sector-specific studies to further elucidate the dynamics of performance management in diverse start-up contexts.